2013
DOI: 10.1073/pnas.1312911110
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-dependent diabetes induced by pancreatic beta cell expression of IL-15 and IL-15Rα

Abstract: Increased serum levels of IL-15 are reported in type 1 diabetes (T1D). Here we report elevated serum soluble IL-15Rα levels in human T1D. To investigate the role of IL-15/IL-15Rα in the pathogenesis of T1D, we generated double transgenic mice with pancreatic β-cell expression of IL-15 and IL-15Rα. The mice developed hyperglycemia, marked mononuclear cell infiltration, β-cell destruction, and anti-insulin autoantibodies that mimic early human T1D. The diabetes in this model was reversed by inhibiting IL-15 sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
55
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 40 publications
4
55
0
1
Order By: Relevance
“…After the treatment, all mice were monitored for spontaneous development of diabetes until 40 weeks of age. The incidence of diabetes onset in ChMBC7-treated mice was significantly lower than that in the control group ( Figure 1B), consistent with previous reports (13)(14)(15)(16). Using the same treatment protocol, separated cohorts of mice were sacrificed at 10 weeks old, and the pancreata were excised and processed for histopathology analysis.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…After the treatment, all mice were monitored for spontaneous development of diabetes until 40 weeks of age. The incidence of diabetes onset in ChMBC7-treated mice was significantly lower than that in the control group ( Figure 1B), consistent with previous reports (13)(14)(15)(16). Using the same treatment protocol, separated cohorts of mice were sacrificed at 10 weeks old, and the pancreata were excised and processed for histopathology analysis.…”
Section: Resultssupporting
confidence: 89%
“…Using the NOD mouse strain, the primary animal model for T1D basic research and preclinical studies (8,17), we showed that a Fc-silent rat/mouse chimeric anti-CD122 mAb (clone ChMBC7) effectively suppressed T1D development, consistent with previous reports (13)(14)(15)(16). Using this engineered anti-CD122 mAb to modulate IL-2/IL-15Rβ signaling, we have investigated how T1D-associated autoimmunity at a prediabetic stage was regulated.…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…15 Recently, we and others have shown that IL-15 plays a crucial role in the pathogenesis of autoimmune type 1 diabetes (T1D). 16,17 In this study, we investigated whether IL-15 trans-presentation plays an essential role in T1D pathogenesis. We show that IL-15Ra deficiency does not affect T1D incidence in two different mouse models and that IL-15Ra is also dispensable for antigen cross-presentation to CD8 1 T cells, and key process in activating autoreactive CD8 1 T cells.…”
Section: Introductionmentioning
confidence: 99%